2016
DOI: 10.2807/1560-7917.es.2016.21.9.30152
|View full text |Cite
|
Sign up to set email alerts
|

The measles outbreak in Bulgaria, 2009–2011: An epidemiological assessment and lessons learnt

Abstract: Measles re-emerged in a nationwide outbreak in Bulgaria from 2009 to 2011 despite reported high vaccination coverage at national level. This followed an eight-year period since the last indigenous cases of measles were detected. The Bulgarian National Centre of Infectious and Parasitic Diseases collated measles surveillance data for 2009–2011. We analysed data for age group, sex, ethnicity, diagnosis confirmation, vaccination, hospitalisation, disease complications, and death and describe the outbreak control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 20 publications
4
11
0
Order By: Relevance
“…This finding is consistent with reported measles cases in Italy, where adults were the most affected age group, with 68% of reported cases aged above 20 years [16–17]. In addition, a number of measles cases in fully vaccinated individuals were also reported in Greece, as well as in outbreaks in other countries [1819] which might be attributed to vaccine failure.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with reported measles cases in Italy, where adults were the most affected age group, with 68% of reported cases aged above 20 years [16–17]. In addition, a number of measles cases in fully vaccinated individuals were also reported in Greece, as well as in outbreaks in other countries [1819] which might be attributed to vaccine failure.…”
Section: Discussionsupporting
confidence: 89%
“…The present study estimation of a significant indirect cost associated with measles-related deaths may be a clear pointer that the disease continues to affect Somalia, especially among children 14 years and younger, robbing off their future productivity and contributions to society. The findings support outcomes of previous studies which reported that measles complications and deaths were disproportionately borne by underage children [37, 38]. The results also relate to the continued global burden of measles in terms of incidence even in developed countries in the European and Western Pacific Regions [39, 40] and in the United States [40, 41].…”
Section: Discussionsupporting
confidence: 89%
“…However, it could still be valuable to show the effect of an outbreak given that such can cause rankings to substantially change from the baseline. For example, the burden of disease was 35.5 DALYs per 100,000 Bulgarian population per year considering the 2010 measles outbreak of just under 22,000 cases [ 34 ]. This burden would have led to this outbreak ranking fourth in our results, between HIV/AIDS and IPD.…”
Section: Discussionmentioning
confidence: 99%